Guided wave scattering behavior in composite bonded assemblies. (February 2016) - Sherafat, Mohammad H.; Guitel, Robin; Quaegebeur, Nicolas; Lessard, Larry; Hubert, Pascal; Masson, Patrice
Abstract: Composite bonded joints are prone to disbond when submitted to fatigue or extreme loads. The objective of this paper is to evaluate the integrity of a composite skin-stringer joint using the scattering behavior of the Lamb waves. The structure of interest is composed of three carbon fiber reinforced polymer (CFRP) plates bonded together by adhesive film as a typical representative of skin-stringer assembly. Two different bonding conditions are investigated for the joint: undamaged and damaged (with disbond). A circular disbond is introduced into the joint using Teflon tape during manufacturing. Two co-localized rectangular piezoceramics are used to generate plane guided waves at 180° and 135° incidence. A non-contact measurement is performed using a 3-D Laser Doppler Vibrometer (LDV) to extract the required information for evaluation of bonding condition. The results present the different scattered field of the guided waves at the joint as a function of frequency, mode, excitation angle and presence of artificial damage. It was found that the amplitude and directivity patterns of scattered fields are affected by the presence of damage, such that SHM design guidelines can be derived for efficient damage detection in the composite skin-stringer bonded joints.